2003
DOI: 10.1016/s0009-2614(03)00820-0
|View full text |Cite
|
Sign up to set email alerts
|

Structure and energetics of Ni clusters with up to 150 atoms

Abstract: We present a method (the Aufbau/Abbau method) for optimizing the structure of a whole series of clusters without making any assumptions on the structure. Subsequently, the method is combined with the embedded-atom method in determining the structure of the two energetically lowest isomers of Ni N clusters with N up to 150. Finally, various analytical descriptors are introduced that are used in studying the overall shape of the clusters, their structure and stability, and possible growth and dissociation proces… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 25 publications
2
51
0
Order By: Relevance
“…Theoretical results are in reasonable agreement with these experimental findings. Different globaloptimization results within semiempirical schemes (Doye and Wales, 1998b;Grygorian and Springborg, 2003) and tight-binding calculations (Lathiotakis et al, 1996) predict fcc and Ih structures at N = 38 and 55 respectively. Moreover, capped Dh structures just above size 38 are found (Andriotis and Menon, 2004;Wetzel and DePristo, 1996).…”
Section: Noble and Quasi-noble Metal Clustersmentioning
confidence: 99%
“…Theoretical results are in reasonable agreement with these experimental findings. Different globaloptimization results within semiempirical schemes (Doye and Wales, 1998b;Grygorian and Springborg, 2003) and tight-binding calculations (Lathiotakis et al, 1996) predict fcc and Ih structures at N = 38 and 55 respectively. Moreover, capped Dh structures just above size 38 are found (Andriotis and Menon, 2004;Wetzel and DePristo, 1996).…”
Section: Noble and Quasi-noble Metal Clustersmentioning
confidence: 99%
“…As we discussed in our earlier report, 39 it is useful to examine the 3 × 3 matrix containing the elements…”
Section: Structural Propertiesmentioning
confidence: 99%
“…In our earlier work 39 we showed that the structural development of the isomer of the lowest total energy with advantage could be monitored through so-called similarity functions. Thus, for a given cluster Ni N we define a radial distance for each of the atoms…”
Section: Structural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…So, this EAM may have a wider range of validity from a few atoms to the larger sizes of the Al n clusters. The EAM grasps the major parts of the interatomic interactions and gives accurate structural and energetic information on various extended and truncated systems [21][22][23]. In the literature Garcia-Rodeja et al [23] used the Voter and Chen version of the EAM by carrying out molecular dynamics (MD) simulations to study the structures and melting of 6 fcc transition metals including Al clusters (Ni, Pd, Al,Cu, Ag, and Au) in the size range of the n = 2 − 23.…”
Section: Introductionmentioning
confidence: 99%